Effects of the Application of Mathematics Learning Media and Cognitive Style on Mathematics Learning Outcomes by Controling the Intial Abilities of Students - Aaltje Pangemanan (Budapest International Research and Critics University, 2022)
This study was aimed to evaluate the effects of mathematics learning media and cognitive styles on mathematics learning outcomes by controlling initial abilities of students. The study was conducted at Public Junior High School 1 and 6 Tondano, Minahasa Regency. The method used was the experimental method with a 2 x 2 factorial design. The sample was grade VII students of Public Junior High School 1 and 6 Tondano where 60 students as samples were obtained based on cluster random sampling. The data were analyzed by analysis of covariance (ANKOVA). The results of the study after controlling the initial abilities of students are as follows: 1) Mathematics learning outcomes of groups of students who employ computer media are higher than those who use teaching aids, 2) Mathematics learning outcomes of groups of students who have independent cognitive field styles are higher than those who have field dependent cognitive style, 3) there is an interaction effect between learning media and cognitive style on learning outcomes, 4) in groups of students who have independent field cognitive styles, the results of mathematics learning groups of students who use computer media are higher than those who use teaching aids media, and 5) in groups of students who use computer media, Mathematics learning outcomes of groups of students who have independent field cognitive styles are higher than those who have field dependent cognitive styles. Therefore, it is expected that mathematics teachers should pay more attention to students cognitive styles and use computer media in learning process.